The Impact of Social and Academic Counseling Guidance on Student Learning Outcomes: The Moderating Role of Interpersonal Skills in Indonesian Islamic Senior High Schools - Dudy Imanuddin Effendi; Lilis Lela Sandy; Ikram Riski; Sitti Saleha binti Samsuddin; Dg Fauziah Binti Datu Ibrahim; Wannadwah Binte Ja'afar (Sakura Digital Nusantara, 2026)
Purpose: Guidance and counseling (GC), especially in its social and academic forms, has been widely acknowledged as a key approach to fostering holistic student development. This study aimed to examine differences in student learning outcomes following the implementation of social and academic counselling at different levels of interpersonal competence: high, medium, and low. Methods: This research utilised a quantitative method, namely a quasi-experimental design. This design incorporated the non-equivalent control group method with a two-way factorial design (2 x 3 ANOVA). The study comprised a sample of 200 students. This research encompassed a cohort of 500 students from a State Islamic Senior High School in Serang Regency, Indonesia. The sample design employed cluster random sampling. The intervention consisted of eight sessions (four academic and four social counseling sessions), each lasting 45–60 minutes, conducted twice a week over a four-week period. Findings: The research findings yield three key results: 1) Variations exist in student learning outcomes following Counseling Guidance (Social and Academic) F=18.654 and Sig.=000 . 2) Variations in student learning outcomes exist based on high, medium, and low interpersonal skills, F=80.655 and Sig.=000. 3) The interaction exists between Counseling Guidance (Social and Academic) and the varying levels of students' interpersonal skills high, medium, and low on student learning outcomes, F=6.451 and Sig.=005. Research implications: This study emphasizes the need for differentiated counseling based on students’ interpersonal skill levels and supports the development of integrated, evidence-based counseling practices in schools. Originality: The primary novelty of this study lies in examining the interaction effect between counseling guidance and students’ interpersonal skill levels on learning outcomes. Unlike prior research that treats these variables independently, this study demonstrates that the effectiveness of counseling guidance varies across students with high, medium, and low interpersonal skills, offering a more nuanced and differentiated of learning.